Protection by vaccination of children against typhoid fever with a Vi-tetanus toxoid conjugate vaccine in urban Bangladesh: a cluster-randomised trial. Issue 10301 (21st August 2021) - Qadri, Firdausi; Khanam, Farhana; Liu, Xinxue; Theiss-Nyland, Katherine; Biswas, Prasanta Kumar; Bhuiyan, Amirul Islam; Ahmmed, Faisal; Colin-Jones, Rachel; Smith, Nicola; Tonks, Susan; Voysey, Merryn; Mujadidi, Yama F; et al.
Summary: Background: Typhoid fever remains a major cause of morbidity and mortality in low-income and middle-income countries. Vi-tetanus toxoid conjugate vaccine (Vi-TT) is recommended by WHO for implementation in high-burden countries, but there is little evidence about its ability to protect against clinical typhoid in such settings. Methods: We did a participant-masked and observer-masked cluster-randomised trial preceded by a safety pilot phase in an urban endemic setting in Dhaka, Bangladesh. 150 clusters, each with approximately 1350 residents, were randomly assigned (1:1) to either Vi-TT or SA 14-14-2 Japanese encephalitis (JE) vaccine. Children aged 9 months to less than 16 years were invited via parent or guardian to receive a single, parenteral dose of vaccine according to their cluster of residence. The study population was followed for an average of 17·1 months. Total and overall protection by Vi-TT against blood culture-confirmed typhoid were the primary endpoints assessed in the intention-to-treat population of vaccinees or all residents in the clusters. A subset of approximately 4800 participants was assessed with active surveillance for adverse events. The trial is registered at www.isrctn.com, ISRCTN11643110. Findings: 41 344 children were vaccinated in April–May, 2018, with another 20 412 children vaccinated at catch-up vaccination campaigns between September and December, 2018, and April and May, 2019. The incidence of typhoid fever (cases per 100 000 person-years) was 635 in JE vaccinees and 96 in Vi-TT vaccinees (total Vi-TT protection 85%; 97·5% CI 76 to 91, p<0·0001). Total vaccine protection was consistent in different age groups, including children vaccinated at ages under 2 years (81%; 95% CI 39 to 94, p=0·0052). The incidence was 213 among all residents in the JE clusters and 93 in the Vi-TT clusters (overall Vi-TT protection 57%; 97·5% CI 43 to 68, p<0·0001). We did not observe significant indirect vaccine protection by Vi-TT (19%; 95% CI −12 to 41, p=0·20). The vaccines were well tolerated, and no serious adverse events judged to be vaccine-related were observed. Interpretation: Vi-TT provided protection against typhoid fever to children vaccinated between 9 months and less than 16 years. Longer-term follow-up will be needed to assess the duration of protection and the need for booster doses. Funding: The study was funded by the Bill & Melinda Gates Foundation.